2011
DOI: 10.1093/annonc/mdq434
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of patients with brain metastases from HER2-positive breast cancer treated with lapatinib and capecitabine

Abstract: LC is active for BMs from HER2+ BC in patients not pretreated with either lapatinib or capecitabine. The introduction of LC after the development of BMs may further improve survival compared with trastuzumab-based therapies only beyond brain progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
3
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(85 citation statements)
references
References 26 publications
9
66
3
7
Order By: Relevance
“…In our study, 23 patients were HER2-positive, and 11 (48%) of them had received lapatinib treatment before enrolling in this trial. The clinical efficacy of the BEEP regimen for the HER2-positive subgroup in our study was higher than that observed in clinical trials in which lapatinib and capecitabine were administered to patients who were previously treated with WBRT (7)(8)(9). In a recent study that was restricted to HER2-positive patients who had not been previously treated with WBRT (24), the clinical efficacy, according to the objective CNS response rate (65.9% according to RECIST) and the median TTP (5.5 months), was similar to that observed in our study.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In our study, 23 patients were HER2-positive, and 11 (48%) of them had received lapatinib treatment before enrolling in this trial. The clinical efficacy of the BEEP regimen for the HER2-positive subgroup in our study was higher than that observed in clinical trials in which lapatinib and capecitabine were administered to patients who were previously treated with WBRT (7)(8)(9). In a recent study that was restricted to HER2-positive patients who had not been previously treated with WBRT (24), the clinical efficacy, according to the objective CNS response rate (65.9% according to RECIST) and the median TTP (5.5 months), was similar to that observed in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…We aimed for a 30% CNS-ORR of the BEEP regimen based on previous studies of brain metastasis of breast cancer patients (7)(8)(9), as well as the traditional view that the efficacy of salvage chemotherapy is expected to be lower in later lines of chemotherapy, which is widely observed in patients who have undergone WBRT. The results demonstrated that the BEEP regimen had a CNS-ORR of 77%, which was considerably higher than expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 In addition, it showed interesting activity in patients with brain metastasis. [4][5][6][7] Skin rash, diarrhea, and hepatic toxicities are adverse events (AEs) that have been linked with not only lapatinib, [8][9][10][11] but also other EGFR TKIs.…”
Section: Introductionmentioning
confidence: 99%
“…При оценке частоты ответа метастазов в ГМ у ранее леченных больных лапатиниб в монотерапии показал эффективность в пределах от 2,6 до 6,0 % [31,32]. При добавлении капецитабина частота ответа воз-растала до 20-33 % [33][34][35][36]. Самая высокая эффектив-ность наблюдалась у ранее не леченных больных: ча-стота объективного ответа при сочетании лапатиниба и капецитабина достигала 65,9 % с медианой времени до прогрессирования 5,5 мес и 1-годичной выжива-емостью > 70 % [37].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified